Faktor-Faktor Yang Mempengaruhi Pendapatan Petani Padi Sawah Di Desa Berangas Kecamatan Alalak Kabupaten Barito Kuala Farmers in Berangas Village Alalak District Barito Kuala Regency - Salsabila, Syifa; Fahraty, Eny (PPJP ULM, 2019)
This research was done to know the influence of land area, seed costs, fertilizier costs,and labour costs simultaneously to income of rice farmer in Berangas Village Alalak DistrictBarito Kuala Regency and to know which variabel is the most dominant influence to the income’s of rice farmers in Berangas Village Alalak District Barito Kuala Regency with fifty-three sampel. This research using multiple linear regression analysis with the help of statistic program application SPSS 23.The results of the regression analysis n this study can be seen that variabel land area,seed costs, fertilizier costs, and labour costs have a simultan effect on farmer income, whilepartially only land area and seed costs, which significantly influence the income of lawland ricefarmer in Berangas Village Alalak District Barito Kuala Regency and fertilizier costs and labourcosts that have no significant effect, and the most dominant variabel affects the income offarmers, namely the variabel cost of seeds based on the value of count which amounted to 4,400tables of 2,021 and greater than the other independent.